2018
DOI: 10.1523/jneurosci.1470-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Phase Synchronicity of μ-Rhythm Determines Efficacy of Interhemispheric Communication Between Human Motor Cortices

Abstract: The theory of communication through coherence predicts that effective connectivity between nodes in a distributed oscillating neuronal network depends on their instantaneous excitability state and phase synchronicity (Fries, 2005). Here, we tested this prediction by using state-dependent millisecond-resolved real-time electroencephalography-triggered dual-coil transcranial magnetic stimulation (EEG-TMS) (Zrenner et al., 2018) to target the EEG-negative (high-excitability state) versus EEG-positive peak (low-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
77
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(89 citation statements)
references
References 56 publications
11
77
1
Order By: Relevance
“…The resulting net facilitation of corticospinal excitability during the asymmetric -alpha oscillation corroborates recent findings of a weak positive relationship between -alpha power and MEP amplitude (Hussain et al, 2018;Thies et al, 2018;Ogata et al, 2019). While the larger excitability for troughs than peaks replicates previous findings (Schaworonkow et al, 2018(Schaworonkow et al, , 2019Stefanou et al, 2018;Zrenner et al, 2018), periods of spontaneous -alpha desynchronization (low power trials) had not yet been considered as baseline to determine the direction of phasic modulation. The only other study taking pre-TMS -alpha power into account used post hoc trial sorting of peaks and troughs and a trial-by-trial linear mixed-effects model to include continuous power values (Hussain et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The resulting net facilitation of corticospinal excitability during the asymmetric -alpha oscillation corroborates recent findings of a weak positive relationship between -alpha power and MEP amplitude (Hussain et al, 2018;Thies et al, 2018;Ogata et al, 2019). While the larger excitability for troughs than peaks replicates previous findings (Schaworonkow et al, 2018(Schaworonkow et al, , 2019Stefanou et al, 2018;Zrenner et al, 2018), periods of spontaneous -alpha desynchronization (low power trials) had not yet been considered as baseline to determine the direction of phasic modulation. The only other study taking pre-TMS -alpha power into account used post hoc trial sorting of peaks and troughs and a trial-by-trial linear mixed-effects model to include continuous power values (Hussain et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…In the primary motor cortex (M1), earlier studies either observed negative relationships in small samples (Zarkowski et al, 2006;Lepage et al, 2008;Sauseng et al, 2009), or no relationship at all (for review, see Madsen et al, 2019), whereas more recent studies suggest a positive linear relationship with motor evoked potential (MEP) amplitude (Hussain et al, 2018;Thies et al, 2018;Ogata et al, 2019). Our group previously observed -alpha phase to modulate corticospinal excitability, with larger MEPs evoked during troughs compared with peaks of -alpha waves (Schaworonkow et al, 2018(Schaworonkow et al, , 2019Stefanou et al, 2018;Zrenner et al, 2018). However, it remained unknown whether this phasic modulation reflects asymmetric pulsed inhibition, asymmetric pulsed facilitation, or a symmetric combination of both (Fig.…”
Section: Introductionmentioning
confidence: 93%
“…Three recent studies, all performed by the same group also used a brain-state triggered EEG-TMS setup to investigate the influence of mu-phase on MEP amplitude [33][34][35]. In contrast with our negative findings, these studies showed significantly larger MEP amplitudes when TMS was given in the trough compared to the peak of the mu-oscillation.…”
Section: On-line Phase-triggered Eeg-tmscontrasting
confidence: 90%
“…EEGinformed phase-dependent TMS was first applied during non-REM sleep [32] and recently applied during resting wakefulness. In highly pre-selected groups of healthy individuals with strong pericentral mu-activity, single-pulse TMS was applied to M1-HAND dependent on mu-phase [33][34][35] or mu-power [36] of the locally expressed mu-activity. These studies found higher MEP amplitudes at the trough relative to the peak of the mu-phase [33,34] as well as higher MEP amplitude in epochs with high relative to low mu-power [36], while no interaction between the two was reported.…”
Section: Introductionmentioning
confidence: 99%
“…In the same frequency-band as parietal alpha, several studies have investigated the influence of mu-phase in motor cortex on motor evoked potential (MEP) amplitude with an EEG-TMS setup. Larger MEP amplitudes were found when TMS was administered at the trough compared to when it was administered at the peak of the mu-oscillation [31][32][33] (but see ref. 34 ).…”
Section: Discussionmentioning
confidence: 99%